Alcuni soffitti lignei in Vaticano tra Pio IV e Gregorio XIII - Balzarotti, Valentina (Opus Incertum, 2018)
This paper analyses some polychrome coffered and carved wooden ceilings of the Palazzo Apostolico (Vatican) undertaken under Pio IV (1555-1559) and Gregory XIII (1572-1585). The study gives specific attention to technique, materials and payments, and analyses the manufacture and decoration of the ceilings in the Sale dei Paramenti and Camera della Falda focusing on the Florentine carpenters Zanobio di Mariotto and Ambrogio Bonazzini.